The Role of Narrow Band Imaging in the Detection of Recurrent Laryngeal and Hypopharyngeal Cancer after Curative Radiotherapy - Zabrodsky, Michal (Hindawi Publishing Corporation, 2014)
Narrow band imaging is considered a significant improvement in the possibility of detecting early mucosal lesion of the upper aerodigestive tract. Early detection of mucosal neoplastic lesions is of utmost importance for patients survival. There is evidence that, especially in patients previously treated by means of curative radiotherapy or chemoradiotherapy, the early detection rate of recurrent disease is quite low. The aim of this study was to prove whether the videoendoscopy coupled with NBI might help detect recurrent or secondary tumors of the upper aerodigestive tract. 66 patients previously treated by means of RT or CRT with curative intent were enrolled in the study. All patients underwent transnasal flexible videoendoscopy with NBI mode under local anesthesia. When a suspicious lesion was identified in an ambulatory setting, its nature was proved histologically. Many of these changes were not identifiable by means of conventional white light (WL) endoscopy. The accuracy, sensitivity, specificity, and positive and negative predictive value of the method are very high (88%, 92%, 76%, 96%, and 91%, resp.). Results demonstrate that outpatient transnasal endoscopy with NBI is an excellent method for the follow-up of patients with carcinomas of the larynx and the hypopharynx primarily treated with radiotherapy.